Access to Specialist Gastroenterology Care in Canada: Comparison of Wait Times and Consensus Targets - Desmond Leddin; David Armstrong; Alan NG Barkun; Ying Chen; Sandra Daniels; Roger Hollingworth; Richard H Hunt; William G Paterson (Canadian Journal of Gastroenterology)
BACKGROUND: Monitoring wait times and defining targets for care have been advocated to improve health care delivery related to cancer, heart, diagnostic imaging, joint replacements and sight restoration. There are few data on access to care for digestive diseases, although they pose a greater economic burden than cancer or heart disease in Canada. The present study compared wait times for specialist gastroenterology care with recent, evidence-based, consensus-defined benchmark wait times for a range of digestive diseases.